Penyelesaian Sengketa Terhadap Pembelian Perumahan Patin Antara Konsumen Dengan PT. Pratama Hutama Jaya Di Pekanbaru - Nexie Nurafifah, Nexie; Firdaus, Firdaus; Firmanda S., Hengki (Fakultas Hukum Universitas Riau, 2026)
This article analyzes dispute resolution in housing purchase transactions between consumers and a housing developer, focusing on the failure to fulfill consumer rights and the effectiveness of dispute resolution mechanisms. The study aims to identify juridical factors causing disputes and to examine how dispute resolution mechanisms operate in practice. This research employs a sociological legal approach by combining primary data obtained through structured interviews and questionnaires with secondary data derived from legal materials and relevant legal literature. The findings indicate that disputes arise primarily from the developer’s lack of transparency in providing accurate information, financial incapacity to complete housing construction, and absence of good faith in fulfilling contractual obligations. Dispute resolution efforts are predominantly pursued through non-litigation mechanisms such as consultation and negotiation. However, these mechanisms have not produced optimal outcomes due to weak commitment from the developer, differences in interests between the parties, and insufficient government supervision. This study contributes to consumer protection discourse by emphasizing the need for stronger supervision, transparency, and good faith in housing development practices to ensure effective protection of consumer rights.